2021
DOI: 10.1186/s12913-021-06131-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer patient’s profile and time to treatment initiation in the public health system in Rio de Janeiro, Brazil

Abstract: Background This paper aims to describe the profile of oral cancer (OC) patients, their risk classification and identify the time between screening and treatment initiation in Rio de Janeiro Municipality. Method Data were obtained from the healthcare Regulation System (SISREG) regarding the period January 2013 to September 2015. Descriptive, bivariate and multivariate analysis were performed identifying the factors associates with a diagnosis of OC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…29 In 2012, a Brazilian federal law 30 established that for patients with a main clinical suspicion of malignant neoplasia, confirmatory exams must be performed within 30 days after medical request and treatment must be started within 60 days after conclusive and histopathologically proven cancer diagnosis. 31 The results of the current study seem to be in accordance with the deadlines established by the law; however, it is noticeable that the patient journey before cancer treatment initiation has not evolved since 2007, 19 evidencing the need to prevent OOC late diagnosis and delayed treatment.…”
Section: Discussionsupporting
confidence: 78%
“…29 In 2012, a Brazilian federal law 30 established that for patients with a main clinical suspicion of malignant neoplasia, confirmatory exams must be performed within 30 days after medical request and treatment must be started within 60 days after conclusive and histopathologically proven cancer diagnosis. 31 The results of the current study seem to be in accordance with the deadlines established by the law; however, it is noticeable that the patient journey before cancer treatment initiation has not evolved since 2007, 19 evidencing the need to prevent OOC late diagnosis and delayed treatment.…”
Section: Discussionsupporting
confidence: 78%
“…RJ is one of the national metropolises, located in this specific region, and has a population of over 6 million. The state also has an extensive network of local government health units, and the headquarters of the National Cancer Institute (INCA) is located in RJ, which is the main reference center for cancer care and research in the country [ 26 ]. Another study has already analyzed the temporal trend in OC mortality rates in RJ and showed a reduction of 1.54% per year in the OC mortality rate from 1999 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the health system, the adult population’s difficult access to dental care and the lack of coordinated actions at the different care levels (primary, secondary, and tertiary) [ 11 , 12 ] can influence the late onset of treatment. The coordination of cancer care involves everything from health policies, organizational aspects of services, appropriate infrastructure, and prepared human resources to socioeconomic issues in the health system context [ 5 ].…”
Section: Introductionmentioning
confidence: 99%